Adrenalin-induced platelet aggregation in essential hypertensive patients in the acute phase of hemispheric ischaemic stroke: LTA results - S. P. Zhemanyuk; V. V. Syvolap (Zaporozhye State Medical University, 2017)
Acquired platelet disorders caused by pathological state or medical induced have pure knowledge according to the experts, especially in essential hypertensive (EH) patients with high and very high cardiovascular risk due to the association with an increased risk of death as stroke and myocardial infarction. The aim of the study was to determine adrenalin-induced platelet aggregation parameters in essential hypertensive patients in acute phase of hemispheric ischaemic stroke. Materials and methods. A total of 98 study participants were analyzed. The first group (n=46; aged 63 (56−71); 38 % man) were well-controlled essential hypertensives according to the «office» and ABMP results, and the second one (n=52; aged 63 (56−71); 66 % man) were EH patients with an acute hemispheric ischaemic stroke (HIS). Light transmittance aggregation (LTA) was conducted with adrenaline (5 μmol/l)).We analyzed the percentage and time of maximal aggregation monitored for 5 and 10 min (Tmax,5minand tTmax,5min, respectively); the percentage of aggregation in 1 min, 2 min, 3 min, 5 min, 10 min (T1min, T2min, T3min, T5min and T10min, respectively); area under the curve at the end of 1, 5 and 10 min periods (AUC1min, AUC5min and AUC10min, respectively); the slope of aggregation (∆T, %/min.); deaggregation at the end of 5 and 10 min periods (Kdesagg,5min andKdesagg,10min,respectively); LTA tracings. Results. There was a decrease of Tmax,5min by 57 % (р=0,028); T1min by 71 % (р=0,002), T2min by 65 % (р=0,002), T3 min by 60 % (р=0,004) and T5min by 59 % (р=0,027); ∆T by 62 % (р=0,002); AUC1min by 84 % (р=0,002), AUC5min by 62 % (р=0,004), AUC10min by 60 % (р=0,018) in group of EH patients with an acute HIS in comparison with the group of well-controlled EH patients. Moreover, as analyzed LTA tracing only so called «considerably decreased» (P=0,020) and «fused» patterns of aggregation (P=0,008) achieved significance in groups. Conclusion. Light transmission aggregometry (optical) with adrenalin (μmol/л) provides the quantitative and qualitative information about the platelet function ability to aggregate in EH patients with and without acute complications. In EHs with an acute HIS there is 57-84% decrease of quantitative parameters in comparison to the same data in well-controlled EHs. Furthermore, they have aggregation patterns which show the different level of the platelet aggregation process reduction, and also there are less so called «fused» patterns of aggregation. We suggested that there is because of treatment which influences substantially the platelet function.